POLICY NETWORK STRATEGY SEBAGAI UPAYA PENGUATAN BRANDING PRODUK-PRODUK UMKM DALAM MENGHADAPI MASYARAKAT EKONOMI ASEAN (MEA) - Rahmi, Purwati Ayu; Ula, Mas; Puspita, Vinanda Karina Dea (Program Kreativitas Mahasiswa - Gagasan Tertulis, 2014)
Preparation and current conditions of the Sector Micro, Small and Medium Enterprises in the ASEAN Economic Community in 2015 is very worthy to be observed. Indonesia has approved a blueprint of the agreement, would not want all of the elements of this nation must work together to face the upcoming challenges. It takes cooperation from various parties to support the economic sector that has been widely credited for Indonesia, SMEs. SME sector development goal is to improve the national economy. However, the need for specific strategies that build the SME sector, especially in strengthening SMEs product branding so widely known by the public. Cooperation between the various parties writer formulated through network policy strategy involving governments, private sector, communities and the establishment of an agency SMEs originating from academia. This policy is focused on how the management of SMEs product branding. One drawback is the poor management of SMEs in each product branding, and therefore a policy is needed to tackle this problem, because if the market is not flooded with Indonesia will continue to foreign products in the upcoming AEC. It is hoped this paper can contribute ideas to the parties concerned so that the SME sector more attention to the efficient and effective policies.Keywords: Policy Network Strategy, Branding, SMEs, MEA